PENATALAKSANAAN FISIOTERAPI PADA GANGGUAN GERAK DAN FUNGSI EKSTREMITAS BAWAH PADA POST OP BONE GRAFT PADA DISTAL FEMUR SINISTRA E.C ANEURYSMAL BONE CYST : CASE REPORT - Arsya Fathinka; W. Wahyuni; Prihantoro Larasati (Jurnal Cakrawala Ilmiah, 2023)
Introduction : Aneurysmal bone cyst (ABC) is a benign bone lesion that can cause localized pain, swelling, and pathological fractures. Treatment of aneurysmal bone cysts (ABC) can be done with traditional measures in the form of intralesional curettage with or without bone grafting. After surgery, postoperative side effects will appear such as incision pain, swelling, decreased muscle strength and limited range of motion (ROM). Purpose : to determine the effect of exercise on reduce pain, increase muscle strength and increase the range of motion of joints Methods : the research method used is a case report. The interventions provided included Isometric Exercise, Stretching, NMES on Quadset, AROM & PROM Exercise, and static loading exercises on the left leg. Results : evaluation of pain scale with NPRS, ROM with goniometer, muscle strength with MMT, range of motion with Goniometer. Conclusions : there is an effect of giving exercise on reducing pain, increasing muscle strength and increasing ROM